Legal Aspects of Merit System Implementation in Civil Service - Ismail, Nurwita; Polontalo, Karim (Universitas Brawijaya, 2025)
The implementation of the merit system in the management of the State Civil Apparatus (ASN) presents a significant legal issue in the context of ongoing bureaucratic reform in Indonesia. This study analyses the legal framework and evaluates the practical application of the merit system following the dissolution of the State Civil Apparatus Commission (KASN). The transfer of supervisory authority to executive institutions has raised legal concerns related to potential overlap of authority, lack of binding control, and weakened legal accountability. Using a combination of normative juridical and socio-legal research methods, the study identifies two key priorities: the necessity of establishing a legally autonomous institution to oversee the implementation of merit principles, and the development of digital competencies among civil servants to support bureaucratic transformation. The research contributes to the field of administrative law by emphasising the importance of legal certainty and institutional independence. For international readers, this study offers insight into the legal challenges of civil service reform in a developing democratic context.